Effectiveness of Gymnastics Dysmenorrhoea and Deep Breathing Relaxation Techniques to Reduce Mensual Pain in Adolescent Women Indonesia - Nofa Anggraini; Ahadiana Restu Suryandari; Rosijah Habibi; Roihatul Jannah; Lussi Kurniati Hidayat; Oom Komariah; Sundari; Adinda Balqis Rachmiyati (Postgraduate, University of Mataram, 2024)
Menstrual pain is a common issue among adolescent girls, often disrupting their daily activities. To address dysmenorrhea, one effective approach is the use of dysmenorrhea exercises and deep breathing relaxation techniques. This study investigates the effectiveness of these methods in reducing menstrual pain among adolescent girls in Indonesia. Utilizing a quasi-experimental design with a pretest-posttest with control group, the research sampled 210 adolescent girls experiencing menstrual pain, selected through purposive sampling. Data was collected via observation sheets and analyzed using paired sample t-tests and independent t-tests. The findings show that before the dysmenorrhea exercises, most participants experienced moderate pain (63.80%), which decreased to mild pain (74.30%) afterward. Similarly, before the deep breathing technique, most participants had moderate pain (76.20%), which reduced to mild pain (58.10%) post-intervention. Both dysmenorrhea exercises (p-value 0.000) and deep breathing techniques (p-value 0.000) were effective in reducing pain, but dysmenorrhea exercises proved more effective. Adolescent girls are encouraged to regularly perform dysmenorrhea exercises and deep breathing techniques for 30 minutes daily during the week leading up to menstruation to manage menstrual pain effectively.